2019
DOI: 10.1080/01621459.2019.1617152
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Space-Time Modeling of Asymptotically Independent Exceedances With an Application to Precipitation Data

Abstract: The statistical modeling of space-time extremes in environmental applications is key to understanding complex dependence structures in original event data and to generating realistic scenarios for impact models. In this context of high-dimensional data, we propose a novel hierarchical model for high threshold exceedances defined over continuous space and time by embedding a space-time Gamma process convolution for the rate of an exponential variable, leading to asymptotic independence in space and time. Its ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
(66 reference statements)
0
25
0
Order By: Relevance
“…For the family Wθ, it might correspondingly be appropriate to assume ν does not vary over some region or, if that did not suffice to produce stable parameter estimates, to assume ν,κ0, and κ1 do not vary. More recent work on environmental extremes often uses hierarchical models to force the scale and shape parameters of the distribution to vary smoothly in space (Bacro, Gaetan, Opitz, & Toulemonde, 2020; Castro‐Camilo, Huser, & Rue, 2019; Sharkey & Winter, 2019; Yadav et al, 2019) and this approach could also be applied to the parametric families proposed here. Such analyses are usually Bayesian and it is not clear what kinds of priors should be put on the parameters as they vary in some spatial index x .…”
Section: Discussionmentioning
confidence: 99%
“…For the family Wθ, it might correspondingly be appropriate to assume ν does not vary over some region or, if that did not suffice to produce stable parameter estimates, to assume ν,κ0, and κ1 do not vary. More recent work on environmental extremes often uses hierarchical models to force the scale and shape parameters of the distribution to vary smoothly in space (Bacro, Gaetan, Opitz, & Toulemonde, 2020; Castro‐Camilo, Huser, & Rue, 2019; Sharkey & Winter, 2019; Yadav et al, 2019) and this approach could also be applied to the parametric families proposed here. Such analyses are usually Bayesian and it is not clear what kinds of priors should be put on the parameters as they vary in some spatial index x .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we always need to choose a finite, and often relatively small, block size, which casts doubts on the validity of the max‐stability assumption in practice. A fast growing body of empirical studies on environmental extremes in the literature has indeed revealed that the max‐stability assumption arising asymptotically is often violated at finite levels (Bopp, Shaby, & Huser, 2020), and that the spatial dependence strength is often weakening as events become more extreme (see, e.g., Bacro, Gaetan, Opitz, & Toulemonde, 2020; Castro‐Camilo & Huser, 2020; Castro‐Camilo, Mhalla, & Opitz, 2020; Davison, Huser, & Thibaud, 2013; Huser, Opitz, & Thibaud, 2017; Huser & Wadsworth, 2020; Tawn, Shooter, Towe, & Lamb, 2018). In particular, under asymptotic independence , maxima become ultimately independent at the highest levels, requiring specialized models capturing the decay rate towards independence.…”
Section: Introductionmentioning
confidence: 99%
“…Let Exp(λ) denote the exponential distribution with rate λ>0, Gamma(α,β) denote the gamma distribution with rate α>0 and shape β>0, that is, with density g(y)={Γ(β)}1αβyβ1exp(αy), y > 0, and GP(τ,ξ) denote the GP distribution with scale τ>0 and shape ξ as defined in (1). Then we have Yfalse|normalΛExpfalse(normalΛfalse)normalΛGammafalse(α,βfalse)YGP(α/β,1/β); see Reiss and Thomas (2007), Bortot and Gaetan (2014, 2016), Bopp and Shaby (2017), and Bacro et al (2020). In other words, exponentially decaying tails become heavier by making their rate parameter Λ random.…”
Section: Introductionmentioning
confidence: 99%